Development of the fishery of northern anchovy (Engraulis mardax) in Baja California from 1972-1992 - R Vidal-Talamantes (Ciencias Marinas, 1995)
The principal changes that occurred in the northern anchovy fishery are analyzed. Data from commercial landings are examined and an explanation of the observed variations in the magnitude and composition of the catch is attempted. The fishery experienced a first phase of increase from 1972 to 1981, followed by a phase of decline in the catch in 1982 and 1983, and a third phase of relative stability of the catch between 1984 and 1989. The age of the fish caught declined in these three periods and there was an increase in the proportion of small-sized fish. The data suggest that the combined effect of the fishery and environmental changes have had an effect on the anchovy population. Since 1990 the landings have been almost null, even though the sardine-anchovy fleet has continued to expend considerable effort in attempting to locate schools. Alternatives for the administration of the resource are proposed. Se analizan los principales cambios ocurridos en la pesquería de anchoveta norteña.